Recruitment of high risk women for HIV prevention trials: baseline HIV prevalence and sexual behavior in the CAPRISA 004 tenofovir gel trial - Karim, Quarraisha Abdool (BioMed Central, 2011)
BACKGROUND: Young women in sub-Saharan Africa bear a disproportionate burden of HIV infection compared to men but have limited options to reduce their HIV risk. Microbicides could fill an important HIV prevention gap for sexually active women who are unable to successfully negotiate mutual monogamy or condom use. PURPOSE: This paper describes the baseline sample characteristics in the CAPRISA 004 trial which assessed the safety and effectiveness of the vaginal microbicide, 1% tenofovir gel for HIV prevention in South Africa. METHODS: This analysis assessed the baseline demographic, clinical and sexual behavior data of women screened and enrolled into the trial. The characteristics were summarized using descriptive summary measures; expressed as means and percent for categorical variables. RESULTS: HIV prevalence at screening was 25.8% [95% Confidence Interval (CI):23.9-27.7). Of the 889 eligibly enrolled women who contributed follow-up data, rural participants recruited from a family planning (FP) clinic were younger, more likely to be living apart from their regular partner, reported lower coital frequency, had lower condom use (p < 0.001). In contrast, urban participants recruited from a sexually transmitted disease (STD) clinic reported higher numbers of lifetime sexual partners, new partners in the last 30 days and receiving money in exchange for sex (p < 0.001). CONCLUSION: The populations selected provide suitable diverse target groups for HIV prevention intervention studies. TRIAL REGISTRATION: ClinicalTrials.gov: NCT 00441298